2014
DOI: 10.1080/1745039x.2014.931522
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and physiological responses of finishing pigs exposed to a permanent heat exposure during three weeks

Abstract: The aim of the current study was to investigate the effect of a permanent heat exposure during 21 days on pig performance, nutrient digestibility, physiological response and key enzyme of skeletal muscle energy metabolism. Twenty-four male finishing pigs (crossbreed castrates, 79.0 ± 1.50 kg body weight) were allocated to three groups (n = 8): (1) Control (ambient temperature (AT) 22°C, ad libitum feeding), (2) Group HE (AT 30°C, ad libitum feeding) and (3) Group PF (AT 22°C, pair-fed to Group HE). The permane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
4
24
1
Order By: Relevance
“…and intrinsic antioxidant system of LD muscle tissues will be downregulated by constant heat stress, mainly because of the destruction of membrane integrity, disorders of neurological function, and the peroxidation of proteins and lipids. Combined with the results of our previous study, there was no significant difference in average daily gain and feed intake between HS and PF groups (Table S2), which were both significantly lower than that in the CR group [47], we can infer that most of the differential expression of metabolites may be due to the reduction of feed intake caused by heat stress, and these changes may not directly affect the growth performance of pigs. We explored the changes in the metabolic profiles of LD muscle under heat stress to provide a basis for research into nutritional strategies for reducing the negative effects of heat stress on livestock and to develop new insights for further research.…”
Section: Discussionsupporting
confidence: 77%
“…and intrinsic antioxidant system of LD muscle tissues will be downregulated by constant heat stress, mainly because of the destruction of membrane integrity, disorders of neurological function, and the peroxidation of proteins and lipids. Combined with the results of our previous study, there was no significant difference in average daily gain and feed intake between HS and PF groups (Table S2), which were both significantly lower than that in the CR group [47], we can infer that most of the differential expression of metabolites may be due to the reduction of feed intake caused by heat stress, and these changes may not directly affect the growth performance of pigs. We explored the changes in the metabolic profiles of LD muscle under heat stress to provide a basis for research into nutritional strategies for reducing the negative effects of heat stress on livestock and to develop new insights for further research.…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies by our research group have demonstrated that chronic HS for 3 weeks in finishing pigs contributes to decreased feed intake and daily body weight gain and increased rectal temperature, respiration rate and plasma cortisol. These parameters are commonly regarded as indicators of the effects of HS on animal physiology.…”
Section: Discussionmentioning
confidence: 96%
“…Pigs dissipate heat poorly, are highly insulated, lack functional sweat glands, and are densely housed during late finishing causing a high risk of susceptibility to HS (White et al, 2008;Qu et al, 2015). Heat stress imposes substantial changes in the physiological status of pigs, such as acid-base homeostasis (Patience et al, 2005) and is noted for suppressing feed intake (Hao et al, 2014; and therefore energy intake of the pig (Renaudeau et al, 2013). Heat stress has a greater impact on pigs with a high rate of lean gain, resulting in reduced carcass lean gain and protein accretion (Nienaber et al, 1997;Brown-Brandl et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvements in barn design, genetics, management, and nutrition, heat stress remains one of the most costly issues for U.S. pork producers (St-Pierre et al, 2003;. To reduce the negative impact of heat stress on energy intake (Hao et al, 2014;, producers formulate diets using ingredients that are energy dense and low in heat increment Stahly et al, 1981). Adding dietary fat has been shown to reduce but by no means completely mitigate the negative effects of HS on ADG (Stahly et al, 1981;Spencer et al, 2005).…”
Section: Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation